A Novel Antimicrobial Hydrogel for the Management of Periodontal Diseases - Pauline Yang Wong; Shane Soo; Edmund Soon-Chern Wong; Praveen Praveen; Peta Clode; Murray V. Baker; Victor Haruo Matsubara (Elsevier, 2023)
Objectives: This study aimed to synthesise a drug-delivery system based on a porous polymer hydrogel, with antimicrobial properties against Porphyromonas gingivalis and potential to be used in tissue regeneration. Material and methods: 2-Hydroxyethyl methacrylate monomers were polymerised using thermal and photoactivation in the presence of silver nitrate (AgNO3) and/or chlorhexidine digluconate. Poly-2-hydroxyethyl methacrylate (pHEMA) hydrogels containing silver nanoparticles (AgNPs) and/or 0.12% chlorhexidine (CHX) were produced and characterised using cryo-SEM and confocal microscopy. Hydrogel degradation and leaching of AgNP were tested for 1.5 months. The antimicrobial properties were tested against P. gingivalis using broth culture system and disk diffusion tests. Results: Our methodology manufactured porous polymeric hydrogels doped with AgNPs and CHX. Hydrogels showed a successful delivery of CHX and sustainable release of AgNPs in a steady hydrogel degradation rate determined based on the weight loss of samples. Hydrogels with AgNPs or CHX had a significant antimicrobial effect against P. gingivalis, with CHX-hydrogels exhibiting a stronger effect than AgNP-hydrogels in the short-term assessment. AgNP-CHX hydrogels showed a compounded antimicrobial effect, whereas control hydrogels containing neither AgNPs nor CHX had no influence on bacterial growth (P < .05). Conclusions: The dual-cured pHEMA hydrogel loaded with antimicrobial agents proved to be an efficient drug-delivery system against periodontopathogens, with the potential to be used as a scaffold for tissue regeneration.